2009
DOI: 10.1016/j.chembiol.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Genetic Identification of Peptidoglycan Inhibitors Potentiating Carbapenem Activity against Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial and community-acquired pathogen for which few existing antibiotics are efficacious. Here we describe two structurally related synthetic compounds that potentiate beta-lactam activity against MRSA. Genetic studies indicate that these agents target SAV1754 based on the following observations: (i) it has a unique chemical hypersensitivity profile, (ii) overexpression or point mutations are sufficient to confer resistance, and (iii) genetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 44 publications
2
91
0
Order By: Relevance
“…Orthologs in some Gram-positive bacteria are also required for PG biosynthesis (29,30). A key finding strengthening the proposal that MurJ is the lipid II flippase in E. coli is the fact that MurJ is a member of the MOP (multidrug/oligo-saccharidyl-lipid/polysaccharide) exporter superfamily (14,16,31).…”
Section: ) (7)mentioning
confidence: 60%
“…Orthologs in some Gram-positive bacteria are also required for PG biosynthesis (29,30). A key finding strengthening the proposal that MurJ is the lipid II flippase in E. coli is the fact that MurJ is a member of the MOP (multidrug/oligo-saccharidyl-lipid/polysaccharide) exporter superfamily (14,16,31).…”
Section: ) (7)mentioning
confidence: 60%
“…However, some key differences in the composition of the stem peptide exist between lipid II from Gram-positive and Gram-negative bacteria (5,34). In addition, there is a low level of conservation between MurJ and YtgP, the putative MurJ ortholog in Gram-positive bacteria (22,35). Given that we have shown that 8 residues within the MurJ cavity region are critical for MurJ function in E. coli, we tested whether these requirements are conserved in YtgP by taking advantage of the fact that ytgP from S. pyogenes complements the depletion of MurJ in E. coli (22).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance in MRSA involves the acquired gene, mecA, which encodes PBP2a, a transpeptidase that functions to cross-link peptidoglycan strands when native transpeptidases are inactivated by β-lactams (4)(5)(6). Many other genes native to S. aureus must be present for mecAmediated resistance to operate (7)(8)(9)(10). Understanding how different factors participate in β-lactam resistance is of paramount importance for developing new approaches to combat MRSA.…”
mentioning
confidence: 99%